Music of the middle ages II - Gallo, Franco Alberto (Cambridge Cambridge University Press, 1985)
This new and illuminating study of medieval polyphony examines the links between music and contemporary political, civil and religious events. The period from the second half of the twelfth century to the second half of the fifteenth is of great historical interest since it marks the development of polyphonic forms and the birth of mensural music. There is also the earliest evidence of individual composers, from Léonin and Pérotin to Machaut, Landini and Dufay. Alberto Gallo pays particular attention to the elaboration of refined techniques of composing, often drawing a parallel with the techniques of rhetoric and poetry. The writing down of music and also theory are shown to be essential stages of composition. Professor Gallo also describes the birth of the professional composer and the flowering of those permanent institutions within which musicians worked and which for centuries characterized European music. Professor Gallo has taken the opportunity of this first English edition to update the text, and to add notes.